Ethical challenges in cancer diagnosis and therapy - Bauer, Axel W.; Hofheinz, Ralf-Dieter; Utikal, Jochen (Recent results in cancer research, 2021)
Cancer as an ethical challenge -- Historical aspects of the „fight against cancer -- One in four dies of cancer.” Questions about the epidemiology of malignant tumors -- Ethical issues related to human papillomavirus vaccination programs: an example from Bangladesh -- Ethical challenges around cell lines in cancer research -- Risk-adapted prevention. Governance perspective for benefits of genetic (breast cancer) risk -- The right to know and not to know: predictive genetic diagnosis and non-diagnosis -- Benefits and harms of cancer screening -- Ethical dilemmas in conducting clinical trials -- Ethical aspects in cancer drug approval, balancing individual versus societal perspectives -- Liver living donation for cancer patients: benefits, risks, justification -- Quality assurance of cancer medication and the challenge of biosimilars -- Cancer in children -- Pain and palliative medicine -- Advance directives for medical decisions -- Euthanasia and assisted suicide -- Doctor's health and the health of caregivers -- Diagnosis breast cancer. An ethnographic study of illness and disease -- The patient’s view -- The patients‘ advocate -- Cancer in literature.